Propofol e fentanil versus midazolam e fentanil para sedação em pacientes cirróticos durante a realização de endoscopia digestiva alta - Correia, Lucianna Motta [UNIFESP] (2012)
Background: Cirrhotic patients often undergo diagnostic or therapeutic upper gastrointestinal endoscopy. The liver cirrhosis might impair the metabolism of drugs used to sedation due to changes in liver function, with possible consequences for the efficacy and safety during procedures. We designed a study to compare two regimens for sedation during endoscopy in this group of patients: propofol with fentanyl and midazolam with fentanyl. Objectives: To compare the two schemes proposed regarding the sedation efficacy (proportion of complete procedures using the initial proposed scheme), safety (occurrence of sedation-related complications) and recovery time (defined as time between the end of the procedure and ambulatory discharge). Patients and methods: We performed a prospective randomized controlled trial conducted between February 2008 to February 2009. Two hundred and ten cirrhotic outpatients were included and randomized in two groups: Midazolam Group (110 patients, 0.05 mg / kg associated with fentanyl, 50 mg intravenously) and Propofol Group (100 patients, 0.5 mg / kg combined with fentanyl, 50 mg intravenously). Results: There were no differences between groups regarding age, sex, weight, etiology of cirrhosis, classification Child-Pugh or ASA classification, as well as to the type of procedure exam was performed (diagnostic test, band ligation or sclerotherapy for esophageal varices). Sedation with propofol and fentanyl was more efficacious (100% vs. 88.2% - p <0.001) and had a shorter recovery time than sedation with midazolam to fentanyl (16.23 ± 6.84min vs. 27.40 ± 17.19 min, respectively - p <0.001). Complications rate were similar in both groups (14% vs. 7.3% - p = 0.172). Conclusion: Both sedation regimens were safe in this setting. Sedation with propofol and fentanyl was more efficacious and had shorter recovery time when compared to midazolam plus fentanyl. Propofol should be considered as an alternative to sedation during upper GI endoscopy in cirrhotic outpatients.